CHANGES OF THE OPTIC DISC SIZE IN PATIENTS WITH EARLY GLAUCOMA AND GLAUCOMA SUSPECTS - A. A. Shpak; M. K. Sevostyanova; S. N. Ogorodnikova (Офтальмохирургия, 2015)
Purpose. To compare optic disk measurements using two devices the HRT 3 and the Cirrus HD-OCT in healthy individuals and glaucoma patients / glaucoma suspec ts.Material and methods. Optic disk parameters were studied using both units in 44 patients – 21 with initial primary openangle glaucoma (POAG) and 23 glaucoma suspects (main group) and 51 healthy individuals of the same sex and age (control group).Results. The disk area measured with the HRT 3 device increased versus to the Cirrus HD-OCT in the main group only. It was accompanied by a similar rim area increase. Disk and rim area increase was especially pronounced in patients with a larger optic disk area.Conclusion. Disk and rim area measured with the HRT 3 device has a relative increase compared to the Cirrus HD-OCT in patients with initial POAG and suspected glaucoma, especially in patients with a larger optic disk area. Such changes could be presumably attributed to the flattening out of the optic nerve head under the influence of increased intraocular pressure.